Sacubitril/Valsartan contributes to improving the diabetic kidney disease and regulating the gut microbiota in mice - Wang, Peipei; Guo, Ruixue; Bai, Xiwen; Cui, Wen; Zhang, Yiding; Li, Huangmin; Shang, Jin; Zhao, Zhanzheng (Frontiers in Endocrinology, 2022)
Background: Diabetic kidney disease (DKD), a serious microvascular complication of diabetes, had limted treatment options. Sacubitril/Valsartan (Sac/Val) is reported to improve kidney function. Gut microbiota dysbiosis and some metabolites were reported to be related with development of DKD. We aimed to explore whether the effect of Sac/Val on DKD is related with gut microbiota and plasma metabolomics. Methods: Male C57BL/6J mice in Con (n = 5) and DKD (n = 6) groups were gavaged with solvent, while Sac/Val (n = 6) group was treated with Sac/Val solution. Results: We found that DKD has significantly higher concentration of serum creatinine compared to the Con group, whereas it was reduced after Sac/Val treatment. Compared with DKD mice, Sac/Val treatment could decrease the expression of indicators related to EndMT and renal fibrosis like vimentin, collagen IV and fibronectin in kidney. LefSe analysis of gut microbiota identified 13 biomarkers in Con group, and 33 biomarkers in DKD group, mainly including Prevotella, Escherichia_Shigella and Christensenellaceae_R_7_group, etc. For the Sac/Val group, there were 21 biomarkers, such as Bacteroides, Rikenellaceae_RC9_gut_group, Parabacteroides, Lactobacillus, etc. Plasma metabolomics analysis identified a total of 640 metabolites, 167 important differential metabolites were screened among groups. KEGG pathway of tryptophan metabolism: M and bile secretion: OS had the highest significance of enrichment. Conclusions: Sac/Val provides protection to DKD through inhibiting fibrosis. This drug can also regulate gut microbiota and plasma metabolism in mice.